EVALUATION OF COc-PHILIC FOA\1 SURFACT ANTS AS \10BILITY CONTROL AGENT - TALEBIAN, SEYEDEH HOSNA (2015)
The focus of this thesis is on the evaluation of C02-philic surfactants for application in foam assisted C02-WAG injection, under immiscible conditions of a Malaysian reservoir case. The surfactant blending and addition of C02-philic functionalities in surfactant structure is investigated for this reservoir to enhance C02 mobility control, and to mitigate SAG operational problems in terms of foam-oil tolerance, limiting water saturation requirement, and sensitivity to reservOir conditions. The C02/oil system phase behavior analysis in tenns of viscosity reduction, IFT reduction, and C02 dissolution in immiscible conditions of the reservoir were experimentally investigated. The structure-property analyses of COr philic surfactant blends were perfonned in terms of C02 dissolution in aqueous phase, effect of surfactant on Oil/Water and Gas/Water interfaces, foamability and foam stability in the presence of oil at reservoir conditions. The theoretical entering, spreading, and bridging coefficients model was utilized for surfactant screening in tenns of foam stability in the presence of oil at desired pressure range and temperature conditions. Foam-induced C02 mobility control for different surfactants was tested in coreflood system to correlate MRF values and interfacial behavior of surfactants.